Establishment of Individual Limited Liability Companies as an Effort for Economic Recovery Due to the Covid-19 Pandemic - Amran; Ibnu Arly (Faculty of Law, Merdeka University Surabaya, 2021)
Purpose of this study is first, to analyze the establishment of a Limited Liability Company PT Individual. Second, to analyze in the establishment of a Limited Liability Company, an individual PT will support economic progress due to the Covid-19 pandemic. This research uses normative legal research methods. This research concludes, first: The establishment of an Individual Limited Liability Company (PT) can be established by an Indonesian citizen, at least 17 years old, the authorized capital of PT Perseorangan, which is at least 25%, then the proof of payment is submitted to the Minister of Law and Human Rights counting 60 ( sixty) days since deed of establishment of the Company for the Company or filling out the Statement of Establishment for an individual Company and this is done electronically. Second: the creation of regulations regarding the establishment of PT. Individuals is expected to be able to support the improvement of the Indonesian economy due to the Covid-19 pandemic, the existence of PT Persorangan targets the middle class, for micro and small businesses.